Navigating public health clinical placements for rural online RN-BSN students - Jill C. Borgos (Rural Nurse Organization; Binghamton University, 2021)
Purpose: In rural settings scare public health resources potentially limits the opportunities for nursing students living in these areas to participate in traditional one to one precepted experiences with public health agencies. To meet the revised Commission on Collegiate Nursing Education Standards related to direct clinical practice, creative strategies are needed for online degree seeking RN-BSN students who live in rural areas. This article explores an alternative learning experience by partnering students with a nonprofit healthcare institute to work on state health initiatives in the geographic region where the students reside. Process: In the absence of adequate opportunities for one to one precepted clinical experiences, student living in rural areas completing an online RN-BS program were partnered with a non-profit health organization. The students participate in an experiential learning experience to fulfill clinical hours in a public health setting as required by the Commission on Collegiate Nursing Education. In this case a cohort of students worked with a nonprofit healthcare institute on New York State's T-21 campaign to further advance their knowledge on health initiatives driven by state health reform policy and actively participate community-based education. Conclusion: With a growing focus on population-based care and caring for vulnerable populations, particularly in rural areas, seeking clinical activities through partnerships with non-profit healthcare institute to improve health outcomes at the community level offers an alternative approach to engaging online degree seeking RN-BSN students in experiential clinical learning in communities with limited public health agency placements. Keywords: interprofessional learning, nursing accreditation, rural nursing students, service-learning pedagogy DOI: https://doi.org/10.14574/ojrnhc.v21i1.664